(untitled) (European Journal of Pure and Applied Mathematics, 2026)
This study investigates the emergency effects of coupling two superconducting-charge-qubits on thermal equilibrium nonlocality behaviors, including Bell inequality violation (BIV) nonlocality and uncertainty-induced (UI) quantum nonlocality beyond logarithmic negativity entanglement (LN entanglement). Thermal entangled two superconducting-charge-qubits states can exhibit UI-quantum nonlocality without BIV nonlocality, highlighting the hierarchical relationship between these resources. Increasing Josephson-qubit energies enhances resistance to degradation at high temperatures. Large differences in Josephson-qubit energies amplify the degradation temperature for nonlocalities. Coupling of the two qubits improves robustness, preservation, and thermal interval of maximal and partial nonlocalities. The temperatures for sudden death of entanglement depend on Josephson qubit energies, their difference, and mutual coupling. Finally, we explore the symmetrical dependence of thermal two superconducting-qubit nonlocality on Josephson-qubit energies and mutual qubit coupling.